The National Acupuncture Detoxification Association protocol, auricular acupuncture to support patients with substance abuse and behavioral health disorders: current perspectives - Stuyt EB; Voyles CA (Dove Medical Press, 2016)
Elizabeth B Stuyt,1 Claudia A Voyles2 1Department of Psychiatry, University of Colorado Health Sciences Center, Pueblo, CO, 2Department of Clinical Studies, AOMA Graduate School of Integrative Medicine, Austin, TX, USA Abstract: The National Acupuncture Detoxification Association (NADA)-standardized 3- to 5-point ear acupuncture protocol, born of a community-minded response to turbulent times not unlike today, has evolved into the most widely implemented acupuncture-assisted protocol, not only for substance abuse, but also for broad behavioral health applications. This evolution happened despite inconsistent research support. This review highlights the history of the protocol and the research that followed its development. Promising, early randomized-controlled trials were followed by a mixed field of positive and negative studies that may serve as a whole to prove that NADA, despite its apparent simplicity, is neither a reductive nor an independent treatment, and the need to refine the research approaches. Particularly focusing on the last decade and its array of trials that elucidate aspects of NADA application and effects, the authors recommend that, going forward, research continues to explore the comparison of the NADA protocol added to accepted treatments to those treatments alone, recognizing that it is not a stand-alone procedure but a psychosocial intervention that affects the whole person and can augment outcomes from other treatment modalities. Keywords: National Acupuncture Detoxification Association (NADA), ear acupuncture, acudetox, addiction, mental health, trauma